Pregnancy care - New South Wales. Aboriginal Health Promotions Section; New South Wales. Department of Health ([New South Wales] : Aboriginal Health Promotions Section, NSW Health Department, 1990)
A colour poster designed as part of an education package about health during pregnancy for Indigenous Australians. Features a central portrait of a pregnant woman and her partner, which is surrounded by captioned photographs which illustrate the themes of good food, daily exercise, partner support, avoid alcohol and smoking, regular check-ups, and a healthy baby. Set on a yellow background with a red and black patterned border. Logos shown at foot of poster: Aboriginal Health Promotions Section; NSW Health Department.
Caption title.
Cultural sensitivity advisory notice: Aboriginal, Torres Strait Islander and other First Nations people are advised that this item may contain images and other content that may be culturally sensitive. Please also be aware that you may see certain words or descriptions within this work which reflect the author’s attitude, or that of the period in which the work was created, and may now be considered inaccurate, inappropriate or offensive.
Keywords: New South Wales. -- Department of Health -- Posters; New South Wales. -- Aboriginal Health Promotions Section -- Posters; Aboriginal Australians -- Health and hygiene -- Posters; Pregnancy -- Australia -- Nutritional aspects -- Posters; Maternal health services -- Australia -- Posters; Public health posters -- Australia; Posters, Australian; Australia -- Posters; Australian